Three-component diels-alder reaction through palladium carbene migratory insertion enabled dearomative C(sp3)-H bond activation - Yiman Mi; Shuoyue Liu; Lingfei Hu; Yihua Wang; Renhui Luo; Yinghua Yu; Zhiyang Zhang; Shan Yuan; Gang Lu; Xueliang Huang (Nature Communications)
Abstract Owning to the versatile nature in participation of Diels-Alder (D-A) reactions, the development of efficient approaches to generate active ortho-quinodimethanes (o-QDMs) has gained much attention. However, a catalytic method involving coupling of two readily accessible components to construct o-QDMs is lacking. Herein, we describe a palladium carbene migratory insertion enabled dearomative C(sp3)-H activation to form active o-QDM species through the cross-coupling of N-tosylhydrazones with aryl halides. The in situ generated o-QDM intermediates were trapped efficiently by 3-nitroindoles and N-sulfonylaldimines to provide dihydroindolo[2,3-b]carbazole derivatives and indole alkaloids modularly. To our knowledge, this reaction represents a rare example on three-component D-A cycloaddition through in situ generation of conjugated dienes by the coupling two readily available materials. We anticipate such a reaction mode could find broad application on diversity oriented six-membered ring construction. Deuterium labeling experiments and density functional theory calculations support a pathway through reversible C(sp3)-H activation to generate heterocyclic o-QDMs.